Activite Antifongique Des Extraits Aqueux De Calendula Officinalis L, Urginea Maritima (L.) Baker Et Chenopodium Ambrosioides L. - Amine, Daoudi; Mohamed, Bammou; Zoubida, Haloui; Jamal, Ibijbijen; Laila, Nassiri (European Scientific Journal, ESJ, 2017)
Fungi are the cause of many human, animal and plant diseases. In the context of valorization of aromatic and medicinal plants of the Central Middle Atlas of Morocco, three plants were selected, based on the results of an ethnobotanical survey in this region, to evaluate their antifungal activity against five Fungi, namely Fusarium oxysporum sp. albedinis, Alternaria sp, Penicillium expansum, Aspergillus brasiliensis and Rhizopus stolonifer. A quantification of the total polyphenols was mesured out for the aqueous extracts of the studied plants Urginea maritima (L.) Baker of the Liliaceae family, Chenopodium ambrosoides L. of the Chenopodiaceae Family and Calendula officinalis L of the Asteraceae family, to choose the form in which the tests will be performed. According to the results, Aspergillus brasiliensis was found sensitive to the macerate of Urginea maritima (L.) Baker at a concentration of 10.71 mg / ml. The percent of inhibition (PI) of mycelial growth was 43.33%. At the same concentration, Fusarium oxysporum showed a slight sensitivity with PI = 19.25%. Furthermore the Chenopodium ambrosoides L decoctate was active against Aspergillus brasiliensis, Alternaria sp and Fusarium oxysporum with PI respectively equal to 41.11%, 40.37% and 27.77%. However, the infusion of Calendula officinalis L showed no effect on the strains tested.